Analysis of a Heighted Multistory Building Frame Considering Sub Base Soil Interaction Considering Lateral Forces - Agrawal, Mayank; Mire, Anisha; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2020)
Lateral forces are now a days considered as the most important load to be applied for designing a tall structure. around the world it has different provisions as per country code but the factor is same to reisst lateral forces and to analyze the structure for concern region zone and base shear. for seismic analysis the most important part to be consider is soil. as soil is the main part from where shakes appears and applied to the structure. In India seismic provision I.S. 1893-I also consider soil effect over the structure. In this research work we are analyzing a G+10 Symmetrical structure which is placed 2 m beneath the soil mass to perform soil structure interaction considering seismic zone IV and soil type consider is soft, medium and hard. It is concluded that soft soil shows low stability and stiffness to the structure as compared to other two type of soil which may cause structure failure and displacement above permissible limit.